Gender Differences in Teachers' Digital Literacy Skills in Teaching STEAM - Moses Adeleke Adeoye (Journal of Education Technology, 2023)
Teachers’ characteristics such as educational level, age, gender, educational experience and digiyal literacy for educational purposes can influence the adoption of an innovation in teaching. This study aimed at analyzing the impact of gender differences on teachers' digital literacy skills in the teaching of STEAM in secondary schools. This study was descriptive research which adopted a Survey type. Four research questions were raised. The population for this research comprised science teachers in Kaduna State secondary schools. A simple random sampling technique was used to select 150 senior science teachers across the three local governments. The questionnaire was designed to elicit information from the senior secondary school teachers on the impact of gender differences on teachers' digital literacy skills in teaching STEAM. Data collected was analyzed using descriptive statistics tools which include pie charts and bar chat. The findings of the study showed that the number of male secondary school teachers was higher than their female counterparts involved in the teaching of STEAM in senior secondary schools. A significant difference exists in the number of male teachers that possess laptop devices compared to their female counterpart. A higher percentage of male teachers possess more digital skills than their female counterpart, lack of school support, limited time and lack of internet access are the major factors affecting the use of digital skills in teaching STEAM. This study recommends that schools should provide the needed facilities required in teaching STEAM based on global best practices.